Induction and amplification of circular dichroism by coupling chiral molecules to achiral plasmonic nanostructured gold films - Xiao-Kang Zhong; Kai-Xiang Liang; Zhen-Long Dou; Qu-Quan Wang; Li Zhou (AIP Advances, 2025)
We present a study on the chiroptical activity modulation of plasmon–molecule hybrids composed of natural chiral molecules and nanostructured gold films. The deposition of chiral riboflavin (vitamin B2) molecules onto nanostructured gold films with varied sputtering time leads to a significant enhancement of extinction and a band shift in the localized surface plasmon resonances, along with fine tuning of the percolating threshold. More interestingly, the circular dichroism (CD) signals of riboflavin are remarkably amplified via plasmonic coupling. Furthermore, this interaction induces a new CD signal emerging around the extinction valley of the gold films in the hybridized system, which is caused by a long-range electromagnetic coupling both with localized surface plasmons and propagating surface plasmon polaritons. The chiral modulation of plasmonic coupling with natural chiral molecules underscores its promising application in the fields of chiral sensing and surface-enhanced spectroscopy.